TEKONOLOGI INFORMASI, SUMBER DAYA MANUSIA, KOMITMEN DAN KOMUNIKASI TERHADAP KESIAPAN IMPLEMENTASI STANDAR AKUNTANSI PEMERINTAHAN BERBASIS AKRUAL - Annisa Intan Pratiwi; Sri Rahayu; Djusnimar Zutilisna (Faculty of Economics and Business, Universitas Pasundan, Bandung, Indonesia, 2017)
The purpose of this study is to determine the effect of information technology, human resources, commitment, and communication to the promptness of the implementation accrual based government accounting standards in Bandung City Government, either simultaneously or partially. The population is the Office of Financial and Assets Management of Bandung City Government. Sampling method used is a saturated sample, as many as 80 respondents. The hypothesis were tested using multiple linear regression analysis. The results showed that information technology, human resources, commitment, and communication have significant effect to the promptness of the implementation accrual based government accounting standards in Bandung City Government simultaneosly. Partially, the information technology, human resources, and communication have positive while commitment does not have significant effect to the promptness of the implementation accrual-based government accounting standard in Bandung City Government.